The Cashless Society Trend: Examining the Influence of e-wallet Usage among Generation Z - Siti Sopiyah; Sriyono Sriyono (International Journal of Islamic Business and Management Review, 2025)
Digital transformation in the era of industrial revolution 4.0 has brought about new phenomena in people's lifestyles, including the shift towards a cashless society. The implementation of social and physical restriction policies has made consumers shift their shopping activities to e-commerce platforms and use digital payment services (e-wallets) more intensively. based on research, mobile banking users are more from Generation Z than Millennials. Young consumers are usually early adopters of technology and can be more innovative. Sometimes Generation Z is more worried about losing their mobile phones than their wallets because almost all transactions can now be done digitally. By using quantitative research techniques with purposive sampling method, the number of samples was 150 respondents with SEM PLS. The results of this study indicate that perceived usefulness, and perceived risk have a positive and significant effect on interest in using e-wallets in Generation Z. Meanwhile, perceived convenience, trust and social influence have no significant effect on interest in using e-wallets among Generation Z.